2007
DOI: 10.1017/s1751731107685073
|View full text |Cite
|
Sign up to set email alerts
|

Early lysine deficiency in young broiler chicks

Abstract: The carry-over effect of a pre-starter diet (0 to 3 days of age) deficient in lysine on subsequent growth and body composition (3 to 10 days) was examined in two experiments on male broiler chicks raised in cages. In experiment 1, lysine deficiency was applied from 3 to 10 days after providing a balanced pre-starter control feed (Dþ, 1.40% lysine) or a lysine deficient feed (D2) during the first 3 days. Three levels of deficiency (A ¼ 0.63%, B ¼ 0.72%, C ¼ 0.82%) were tested. Growth and feed intake were higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
(35 reference statements)
2
7
0
Order By: Relevance
“…However, this reduction of body weight gain was not due to a reduced food intake as, relative to their metabolic active mass, deficient rats have an increased food and energy intake. Rats submitted to severe deficiency of either lysine or threonine showed increased relative food and energy intake but lower BW gain, leading to a null (for lysine) or negative (for threonine) food efficiency, as previously observed for lysine in gilt [ 9 ], chick [ 10 ] and mice [ 6 ], and for threonine in Pekin ducks [ 12 ] and rats [ 6 ]. However, Yap et al 2020, reported in mice that threonine induced a food inefficiency sufficient enough to mimic the effects of dietary EAA restriction, they did not observe any effect of lysine deficiency [ 6 ].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, this reduction of body weight gain was not due to a reduced food intake as, relative to their metabolic active mass, deficient rats have an increased food and energy intake. Rats submitted to severe deficiency of either lysine or threonine showed increased relative food and energy intake but lower BW gain, leading to a null (for lysine) or negative (for threonine) food efficiency, as previously observed for lysine in gilt [ 9 ], chick [ 10 ] and mice [ 6 ], and for threonine in Pekin ducks [ 12 ] and rats [ 6 ]. However, Yap et al 2020, reported in mice that threonine induced a food inefficiency sufficient enough to mimic the effects of dietary EAA restriction, they did not observe any effect of lysine deficiency [ 6 ].…”
Section: Discussionsupporting
confidence: 65%
“…Indeed, a diet low in all EAA (but adequate in all non-essential amino acids) was able to reproduce the effects of a protein-deficient diet on body weight, food intake, and energy expenditure [ 2 , 6 , 8 ]. A diet deficient in only one EAA has been shown to alter growth [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], increase or decrease food intake [ 6 , 9 , 10 , 11 , 12 , 13 , 15 , 16 , 18 , 21 ], modify body composition [ 9 , 10 , 12 , 13 , 15 , 16 , 17 , 18 , 21 , 22 ], and change or not energy expenditure [ 6 , 18 , 22 ]. However, the implication of one or several specific amino acids (AA) during protein deficiency was mainly investigated with a restricted number of EAA and few levels of deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary lysine concentrations have a large influence on breast muscle development (Kerr et al 1999). It has been reported that low-lysine diet not only leads to poor performance but also reduces breast muscle yield (Kidd 2004;Bastianelli et al 2007). This could be the reason that higher breast meat yield was observed in the dietary group where QPM was replaced with RM at 50% or higher level.…”
Section: Discussionmentioning
confidence: 99%
“…Urdaneta- Rincon and Leeson (2004) have shown that the increasing of fractional rate of protein synthesis (FSR) parallel with the increasing of diet lysine levels at 290 g of CP/kg. For fast growing broiler chicks, lysine deficiency have changed body composition and protein synthesis (Ojano-Dirain and Waldroup, 2002;Bastianelli et al, 2007). It means that to support optimum growth and carcass yield of fast-growing commercial broilers, adequate dietary levels of amino acids are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Tomas et al (1988) suggested that selection has been done to improve feed utilization efficiency in oeder to reduce the rate of skeletal muscle protein degradation as measured by 3-methyl histidine excretion, whilst selection to increase growth rate or to reduce body fatness have been shown increasing gross protein utilization efficiency (Geraert et al, 1987;McLeod et al, 1988, Tomas andPym, 1995). Differences in growth performance and nutrient utilization between commercial strains of broilers, may be due to the differences in protein utilization efficiency and genetic differences influence the response of chicks to varying dietary level of crude protein (Ojano-Dirain and Waldroup, 2002;Sterling et al, 2003;Sterling et al, 2006;Bastianelli et al, 2007). Derivative of the amino acid, and histidine nare found mainly in the contractile proteins of muscle (myosin and actin).…”
Section: Introductionmentioning
confidence: 99%